Vestibular physiology and function in zebrafish - Baeza-Loya, Selina; Raible, David W. (Frontiers in Cell and Developmental Biology, 2023)
The vestibular system of the inner ear provides information about head motion and spatial orientation relative to gravity to ensure gaze stability, balance, and postural control. Zebrafish, like humans, have five sensory patches per ear that serve as vestibular peripheral organs, with the addition of the lagena and macula neglecta. The zebrafish inner ear can be easily studied due to its accessible location, the transparent tissue of larval fish, and the early development of vestibular behaviors. Thus, zebrafish are an excellent model for studying the development, physiology, and function of the vestibular system. Recent work has made great strides to elucidate vestibular neural circuitry in fish, tracing sensory transmission from receptors in the periphery to central computational circuits driving vestibular reflexes. Here we highlight recent work that illuminates the functional organization of vestibular sensory epithelia, innervating first order afferent neurons, and second order neuronal targets in the hindbrain. Using a combination of genetic, anatomical, electrophysiological, and optical techniques, these studies have probed the roles of vestibular sensory signals in fish gaze, postural, and swimming behaviors. We discuss remaining questions in vestibular development and organization that are tractable in the zebrafish model.